It Was Like My Trying to Have a Tender-Hearted Nature : A Novella and Stories - Williams, Diane, 1946- (Book collections on Project MUSE., 2007)
A collection of forty-one stories and novella, this work probes the dangerous terrain of the family romance and the eternal bafflement of being alive.